IMPLEMENTASI KEBIJAKAN PENILAIAN KOMPETENSI PEMERIKSA DI BPK RI PERWAKILAN PROVINSI JAWA BARAT - MUHAMMAD INDRA YANUAR ADITYA; Teni Listiani; Sait Abdullah (JRPA - Journal of Regional Public Administration, 2023)
This research examines about the implementation of auditor competence assessment policy at the Audit Board of the Republik of Indonesia (BPK) to assess the competence of auditors in conducting audit that produce high quality and provide recommendations for the managements and accountability of state finances in achieving national goals. The objectives of this research are to analyzing the implementation of auditor competence assessments policy at the Representative Office in West Java, analyzing the factors that support and hinder the implementation and provide an alternative implementation model for improving the success of the auditor competence assessment policy implementation. The research approach used is a qualitative approach with data collection techniques including observation, interviews, and secondary data and the data validity is tested through source triangulation. The results of the research show that there are factors that hinder the implementation, including the limited number of classes used for role training, the timing of role training that may not be suitable, and the lack of understanding between examiners and auditors in explaining audit experiences. These hindering factors can be addressed through the utilization of digital media like online classes and involving senior auditors as a mentor for the examination team to explain the alternative audit procedures.